Building energy and environmental modelling. (CIBSE applications manual, 1998)
The task of designing services within buildings is now frequently carried out using building energy and environmental modelling (BEEM) software. There are however, many aspects to consider when using modelling software and the systems available will produce widely differing results depending on how they are used. AM11: Building energy and environmental modelling ensures a better understanding of the technology. It is especially focused on the modelling of thermal, airflow and lighting performance in buildings and will help you to ensure that you achieve appropriate results from your software. --